Breaking with Tradition: A Scoping Meta‐Analysis Analyzing the Effects of Student‐Centered Learning and Computer‐Aided Instruction on Student Performance in Anatomy. Issue 1 (16th April 2018) - Wilson, Adam B.; Brown, Kirsten M.; Misch, Jonathan; Miller, Corinne H.; Klein, Barbie A.; Taylor, Melissa A.; Goodwin, Michael; Boyle, Eve K.; Hoppe, Chantal; Lazarus, Michelle D.
Abstract : While prior meta‐analyses in anatomy education have explored the effects of laboratory pedagogies and histology media on learner performance, the effects of student‐centered learning (SCL) and computer‐aided instruction (CAI) have not been broadly evaluated. This research sought to answer the question, "How effective are student‐centered pedagogies and CAI at increasing student knowledge gains in anatomy compared to traditional didactic approaches?" Relevant studies published within the past 51 years were searched using five databases. Predetermined eligibility criteria were applied to the screening of titles and abstracts to discern their appropriateness for study inclusion. A summary effect size was estimated to determine the effects of SCL and CAI on anatomy performance outcomes. A moderator analysis of study features was also performed. Of the 3, 035 records screened, 327 underwent full‐text review. Seven studies, which comprised 1, 564 participants, were included in the SCL analysis. An additional 19 studies analyzed the effects of CAI in the context of 2, 570 participants. Upon comparing SCL to traditional instruction, a small positive effect on learner performance was detected (standardized mean difference (SMD = 0.24; [CI = 0.07, 0.42]; P  = 0.006). Likewise, students with CAI exposure moderately outscored those with limited or no access to CAI (SMD = 0.59; [CI = 0.20, 0.98]; P  = 0.003). Further analysis of CAI studies identified effects ( P  ≤ 0.001) for learner population, publication period, interventional approach, and intervention frequency. Overall, learners exposed to SCL and supplemental CAI outperformed their more classically‐trained peers as evidenced by increases in short‐term knowledge gains. Anat Sci Educ. © 2018 American Association of Anatomists.